Pengaruh Substitusi Artemia spp. dengan Keong Mas (Pomacea canaliculata) dan Cacing Tanah (Lumbricus rubellus) Terhadap Pertumbuhan dan Retensi Protein Benih Ikan Gabus (Channa striata) [Substitution Effect Of Artemia spp. With Golden Snail (Pomacea canaliculata) and Worm (Lumbricus rubellus) On The Growth and Protein Retention Snakehead Seed (Channa striata) ] - Moch. Amin Alamsjah; Ditari Kurnia D.; Epy Muhammad Luqman (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Freshwater culture commodity such as snakehead fish (C. striata) has high sufficient demand. Attempts for maintaining snakehead fish population (C. striata) has been done by cultivating. Natural feeding form Artemia spp. can increase the survival rate of snakehead fish seed (C. striata), but the usage of Artemia spp. make farmers pay high cost that it can cause loss. This study aimed to determine the effect of substitution of Artemia spp. with golden snails (Pomacea cancaliculata) and worm (Lumbricus rubellus) on the growth and protein retention of snakehead fish seed. Methods that used in this study is experimental method, with Completely Randomized Design (RAL) as an experimental design. Treatment is given in the form of nine different types of feed that includes, P0 treatment with Artemia spp., P1 with worm feed (L. rubellus), P2 with golden snail feed (P. cannaliculata), P3 with feed Artemia spp. 75% and worm (L. rubellus) 25%, P4 with feed Artemia spp. 50% and worm (L. rubellus) 50%, P5 with feed Artemia spp. 25% and worm (L. rubellus) 75%, P6 with feed Artemia spp. 75% and golden snail (P. cannaliculata) 25%, P7 with feed Artemia spp. 50% and golden snail (P. cannaliculata) 50%, P8 with feed Artemia spp. 25% and golden snail (P. cannaliculata) 75%. Each treatment was repeated three times. Data analysis using analysis of variance (ANOVA). The results showed that substitution Artemia spp. with golden snail (P. canniculata) with worm (L. rubellus) doesn't give real effect (P>0.05) to the growth and protein retention of seed snakehead fish (C. striata). The average of daily growth rate (SGR) 1.60-1.889%, average absolute growth 1.2391.522cm and protein retention 40.664-49.406%. The results showed that golden snail (P. canniculata) and worm (L. rubellus) can be used as substitution feed of Artemia spp. for snakehead fish (C. striata).